Design concept of in-pipe hydro system prototype for renewable energy generation: Vertical axis parallel turbines / Muhammad Fazrin Abdullah - Muhammad Fazrin, Abdullah (2021)
A new design concept for in-pipe hydropower generation is proposed to optimally harness power from the flowing water in a pipe without having to fully block or divert the main water flow, while at the same time makes maintenance work doable without having to stop the whole operating system. The experiment was first conducted to evaluate the performance of the specially designed nozzle and turbine set to get the most optimum performance, using a water pump with a flow rate of 0.48 m3/min. After getting the most optimum condition for the nozzle and turbine set, the actual prototype was fabricated based on a water pipe of 5-inch diameter. The prototype was then tested using a water pump with a maximum flow rate of 4.4 m3/min and maximum water pressure of 1.4 Bars. The maximum value of water pressure is measured by fully closing the pipe while running the water pump at maximum speed. The speed of the water pump is adjustable using a variable speed drive (VSD). Under the best condition, the differential pressure at P1 (The value of water pressure before the prototype) and P2 (The value of water pressure after the prototype) was 0.29 Bars. The percentage of pressure loss or the ratio between the value of pressure (P1 – P2) and the total pressure inside the pipe was 20.7%. The electrical power generated from the in-pipe hydropower system was 1 kW. Based on the study, the in-pipe hydropower system developed here is proven to be workable for inpipe hydropower generation. At the same time, the system can also act as an alternative for a pressure relief valve (PRV).